POLITIK HUKUM PENGEMBALIAN KETETAPAN MAJELIS PERMUSYAWARATAN RAKYAT DALAM HIRARKI PERATURAN PERUNDANG-UNDANGAN BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 2011 TENTANG PERATURAN PERUNDANG-UNDAGAN DI INDONESIA - Jendri Heri Sumarta; Dodi Haryono; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The structure of a legal state in principle is a way to create a complex legal system, to realize the legal order that governs the relationship between the communities by the state or state institutions in a region or country. Hans Kelsen in his book entitled "General Theory of Law and state" suggests a theory known as the "Stufen theory". In the essence of this theory assert legal hierarchical, structured shows that law subordinate must not conflict with the law who are in it or a higher degree. Historical development hierarchy Laws and Regulations in Indonesia started since 1966 in the form back to the Regulation of Legislation No. 12 in 2011. In 1996, by the provisions of the People's Consultative Assembly (MPR) Number. XX / MPR / 1966 Appendix 2, stated that the Hierarchy of Laws and Regulations Indonesia. Considering need to reform of legal products to fit the needs of the people so, that the law not only as a complement to the administration of the state alone but also have a very important role in advancing Indonesian state administration as well as increased development of the public to be more developed in accordance with the demands of the times.So based on the above-mentioned background writer interested in studying due to the recurrence of People's Consultative Assembly provisions in the legislation hierarchy after the enactment of Law No. 12 Year 2011 on the Establishment of legislation, raises various questions, regarding the position of the People's Consultative Assembly re-provision , the writer put it in the form of a thesis with the title, "Political Law of the People's Consultative Assembly Decree Returns in Hierarchy of Laws and Regulations Under Law No. 12 of 2011 Concerning the Establishment of Laws and Regulations in Indonesia"Keywords: Politics Returns Law of the People's Consultative Assembly Decree Based on Law No. 12 of 2011